Implementation Of Academic Supervision To Improve Teacher's Professional Competence - Elismarwati (Institute of Computer Science (IOCS), 2022)
This study discusses the implementation of academic supervision of supervisors in improving the professional competence of teachers of Islamic subjects at Madrasah Ibtidaiyah Negeri 4, Central Bengkulu Regency. The objectives of this research are: (1) to describe and analyze the process of planning, implementing, evaluating, and following up on the implementation of supervisory and academic supervision; and (2) to describe and analyze the inhibiting factors in the process of implementing academic supervision. This type of research is qualitative field research using a descriptive approach. Data collection techniques with the method of interview, observation, and documentation. The results showed that the process of implementing academic supervision of supervisors, when viewed from the planning aspect was considered suitable because before carrying out supervision activities, supervisors first made plans such as Academic Supervision Plans, Annual Programs, Semester Programs, and others. The supervisor's academic supervision was carried out two times. Overall, the Academy Supervision Plan program has been realized in the field. Evaluation and follow-up of academic supervision programs are conducted after learning observations in class or through meetings, Subject Teacher Deliberation activities, training activities, training, or workshops. The obstacles experienced by supervisors in implementing supervision are the number of teachers and schools that must be fostered, the lack of academic supervision of teachers, and some teachers who teach not per the lesson plan. The need to expand the number of school supervisors to match the number of instructors and schools being supervised is indicated by obstacles discovered by school supervisors during the execution of monitoring. There should be more teacher training available.